Representasi Kemandirian Dalam Film (Studi Analisis Semiotika Representasi Kemandirian Pada Tokoh Enola Dalam Film “Enola Holmes”) - Reydea Nur Istya; Dyva Claretta (Journal Education Innovation (JEI), 2024)
Adolescents who are vulnerable to environmental influences will influence how they will face problems in their lives, but the independent character that is formed from an early age can make adolescents easily determine their life path without influence from other people. The aim of this research is to find out how the character Enola represents independence in the film Enola Holmes, and to collect research data using documentation and observation. The research results show that each individual has their own driving factors for independent character according to their environment. Independent factors that can influence a person are parenting patterns, age, education, birth order, gender, intelligence and social interactions. If an individual obtains all of these factors well and positively, then that individual will have a character who is able to take responsibility, and be able to face life's problems without the help of other people, and will also be able to make decisions well and correctly according to the self-confidence she has.